Assessment of the nutritional status and factor associated with children under 5 in remote areas at Don Duong district, Lam Dong province. (Vietnam Journal of Community Medicine, 2021)
A cross-sectional study established the nutritional status (wasted status) and factors associated with children under 5 years old living in remote areas, Don Duong district, Lam Dong province, 2019. The results showed: the percentage of underweight was 19.3%. There are several factors associated with the nutritional status included: Iron-folic tablet consumption, social-economic status of family, birth weight, breastfeeding, vitamin A consumption, sick child nursing.